Biodiesel production from municipal wastewater treatment plant sludge by direct liquid - liquid lipid extraction method - Alper, Dilek Atik. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2019)
Energy plays a significant role in sustaining the modern society. Currently, most of the energy demand is satisfied from fossil sources which are non-renewable and cause environmental problems. In order to eliminate these problems, biodiesel is accepted to be the best alternative energy source as it can be used directly without requiring any kind of modification and it is harmless to the environment. Biodiesel production is not expanded because of high raw material costs. Thus, it is essential to find a cheap alternative feedstock, uncompetitive with food market and easily available in large quantities. Municipal wastewater treatment plant (WWTP) sludges have high lipid content and can be used as feedstock for biodiesel production. The aim of the study was explore the lipid extraction efficiency for biodiesel production from municipal WWTP sludges by using the novel direct liquid-liquid lipid extraction method eliminating the expensive dewatering and drying steps and compare it with standard lipid extraction method. The study also comparatively investigated the effects of acid, ultrasonic and microwave pretreatments on the lipid and biodiesel yields. The results of the study showed that the primary sludge is better lipid feedstock for biodiesel production compared to secondary sludge. Although higher lipid yields were attained from primary sludge using the standard method compared to the direct liquid-liquid lipid extraction method, almost the same biodiesel yields were achieved by both of the extraction methods. Acid pre-treatment increased the lipid and biodiesel yields. The highest increasing impact was obtained by the application of combined acidification/ultrasonication pretreatment.
Keywords: Biodiesel fuels industry.; Wastewater.; Sewage sludge.; Sewage disposal plants.